Application and development of 3D bioprinting in cartilage tissue engineering. (16th August 2022) - Li, Mingyang; Sun, Daocen; Zhang, Juan; Wang, Yanmei; Wei, Qinghua; Wang, Yanen
Abstract : Bioprinting technology can build complex tissue structures and has the potential to fabricate engineered cartilage with bionic structures for achieving cartilage defect repair/regeneration. Abstract : Articular cartilage defects are one of the most common clinical diseases of bone articulation. Early repair of damaged joint cartilage can effectively stop the progression of arthritis and restore health to the patient. In recent years, various therapeutic strategies have been developed to repair cartilage defects and make them available for clinical transplantation. However, cartilage defect repair remains a clinically unsolved challenge to date. Although there have been numerous breakthroughs in cartilage defect repair, the limited spatial complexity of tissue-engineered implants in terms of cells, materials, and active factors has limited the success of engineered cartilage so far. Bioprinting technology allows for the construction of three-dimensional tissues drop by drop and layer by layer, where cells, matrices, and active materials can be deposited on demand while maintaining high precision. Therefore, adopting the bioprinting technology in cartilage tissue engineering promises to develop the next generation of engineered cartilage and address the cartilage defect/regeneration problem. In this paper, we reviewed the bioinks and bioprinting technologies used in cartilage tissue engineering, outlined the recent advances of 3D bioprinting technologies in cartilage tissue engineering, and prospected the development direction of next-generation engineered cartilage.